Moderne Litevska Fotografie. - Jurenaite, Raminta; Soros Center for Contemporary Arts, Vilnius (Praha : Prague City Gallery, 1999)
Stanionis, Vytautas ; Sutkus, Antanas ; Machauskas, Aleksandras ; Rakauskas, Romualdas ; Pozerskis, Romualdas ; Kazlauskas, Juozas ; Stoskus, Kestutis ; Aleksandravicius, Algimantas ; Kuncius, Algimantas ; Trimakas, Gintautas ; Budvytis, Alfonsas ; Lukys, Alvydas ; Bubelyté, Violeta ; Michelkeviciute, Snieguole
biografie
Moderne Litevska Fotografie / Moderna Litovska Fotografia / Contemporary Lithuanian Photography / Litauische Moderne Photographie, Gallery Hlavniho mesta Prahy (Prague City Gallery), November, Month of Photography, Bratislava, 1999
Tsjechisch & Slovaaks & Engels & Duits
boek
Keywords: Litouwen